2024
DOI: 10.1186/s13756-024-01372-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, regional distribution, and trends of antimicrobial resistance among female outpatients with urine Klebsiella spp. isolates: a multicenter evaluation in the United States between 2011 and 2019

Keith S. Kaye,
Vikas Gupta,
Aruni Mulgirigama
et al.

Abstract: Background Antimicrobial resistance research in uncomplicated urinary tract infection typically focuses on the main causative pathogen, Escherichia coli; however, little is known about the antimicrobial resistance burden of Klebsiella species, which can also cause uncomplicated urinary tract infections. This retrospective cohort study assessed the prevalence and geographic distribution of antimicrobial resistance among Klebsiella species and antimicrobial resistance trends for K. pneumoniae in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This study adds to our previous findings regarding AMR prevalence among E. coli and Klebsiella species ( Klebsiella spp.) isolates in the US [ 11 , 13 ]. The current study also provides much-needed multicenter AMR surveillance data and highlights the importance of assessing patterns of co-resistance among uropathogens causing community-acquired UTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adds to our previous findings regarding AMR prevalence among E. coli and Klebsiella species ( Klebsiella spp.) isolates in the US [ 11 , 13 ]. The current study also provides much-needed multicenter AMR surveillance data and highlights the importance of assessing patterns of co-resistance among uropathogens causing community-acquired UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously reported that 14.4 and 3.8% of E. coli isolates have ≥ 2 and ≥ 3 drug resistance phenotypes, respectively [ 11 ], while more than 10% of Klebsiella spp. and K. pneumoniae isolates have ≥ 2 drug resistance phenotypes [ 13 ], but these new analyses of co-resistance among resistant isolates highlight the limitations of the currently available uUTI antibiotics. Raising awareness of antimicrobial co-resistance phenotypes should help inform empiric treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae is considered to be one of the most important opportunistic pathogens responsible for NIs including sepsis, soft tissue infections, pneumonia [168], and UTIs, which are the most common worldwide [169]. K. pneumoniae is implicated in 6-17% of opportunistic UTI cases mainly linked to bacterial adhesion in the inner and outer surfaces of the urinary catheter [170,171]. Moreover, it is the second pathogen involved in BSIs, after E. coli [172].…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%